2017
DOI: 10.1002/smj.2630
|View full text |Cite
|
Sign up to set email alerts
|

Let them go? How losing employees to competitors can enhance firm status

Abstract: Research summary:Because employees can provide a firm with human capital advantages over competitors, firms invest considerably in employee recruiting and retention. Departing from the retention imperative of strategic human capital management, we propose that certain employee departures can enhance a firm's competitiveness in the labor market. Specifically, increased rates of career-advancing departures by a firm's employees can signal to potential future employees that the firm offers a prestigious employmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 91 publications
2
28
0
Order By: Relevance
“…Departures of employees who had relationship conflicts can better the quality of social relationships in the organization overall which increases social capital by reducing relational conflict. Moreover, Tan and Rider (2017) suggested that if firms help employees leave for high-status jobs at other organizations, they are likely to attract more high-potential employees, which ultimately builds social capital and creates new social relationships at work. Future research should model recursive turnover giving consideration to conditions that produce a net positive effect within the organization versus a net negative effect.…”
Section: Advancing Relational Turnover Theorymentioning
confidence: 99%
“…Departures of employees who had relationship conflicts can better the quality of social relationships in the organization overall which increases social capital by reducing relational conflict. Moreover, Tan and Rider (2017) suggested that if firms help employees leave for high-status jobs at other organizations, they are likely to attract more high-potential employees, which ultimately builds social capital and creates new social relationships at work. Future research should model recursive turnover giving consideration to conditions that produce a net positive effect within the organization versus a net negative effect.…”
Section: Advancing Relational Turnover Theorymentioning
confidence: 99%
“…Other aspects like limited opportunities for career growth versus the availability of better jobs that offer the desired opportunities for personal growth and non-appreciation of employees by the management can be strong push factors. However, Tan and Rider, (2017) embrace departure of employees to rival companies as prestigious saying it is an advancement for competitors and it serves the benefit of career growth. Additionally, the inability of the supervisors and the management to resolve employer-employee conflicts is another factor in this case (Pinnington, Macklin, & Campbell, 2007, p. 141).…”
Section: General Roles Of Hrm In Talent Management and Retentionmentioning
confidence: 99%
“…Accordingly, we posit that high-capability workers may be perceived to be less motivated by an employer’s objectives. Second, previous work has suggested that candidates with higher-capability signals will be more mobile and thus have more alternative job opportunities (Coles et al, 2010; Bidwell et al, 2015; Tan and Rider, 2017), reducing the likelihood that such a high-capability candidate will stay with the firm (Johnson and Johnson, 1996, 2000). Thus, our theoretical argument is that signals that increase perceptions of capability above a threshold of sufficiency also decrease the level of perceived commitment, because they raise concerns about the potential for misalignment between organizational goals and a candidate’s effort on the job and about the candidate’s future desire to take advantage of outside employment opportunities associated with high-capability signals.…”
mentioning
confidence: 99%